Cultural Differences in Affect Intensity Perception in the Context of Advertising - Pogosyan, Marianna; Engelmann, Jan B. (Frontiers in Psychology, 2011)
Cultural differences in the perception of positive affect intensity within an advertising context were investigated among American, Japanese, and Russian participants. Participants were asked to rate the intensity of facial expressions of positive emotions, which displayed either subtle, low intensity, or salient, high intensity expressions of positive affect. In agreement with previous findings from cross-cultural psychological research, current results demonstrate both cross-cultural agreement and differences in the perception of positive affect intensity across the three cultures. Specifically, American participants perceived high arousal (HA) images as significantly less calm than participants from the other two cultures, while the Japanese participants perceived low arousal (LA) images as significantly more excited than participants from the other cultures. The underlying mechanisms of these cultural differences were further investigated through difference scores that probed for cultural differences in perception and categorization of positive emotions. Findings indicate that rating differences are due to (1) perceptual differences in the extent to which HA images were discriminated from LA images, and (2) categorization differences in the extent to which facial expressions were grouped into affect intensity categories. Specifically, American participants revealed significantly higher perceptual differentiation between arousal levels of facial expressions in high and intermediate intensity categories. Japanese participants, on the other hand, did not discriminate between high and low arousal affect categories to the same extent as did the American and Russian participants. These findings indicate the presence of cultural differences in underlying decoding mechanisms of facial expressions of positive affect intensity. Implications of these results for global advertising are discussed.